O caso Curt Lange : análise de uma polêmica (1958-1983) - Remião, Cláudio Roberto Dornelles (2018)
The present doctoral dissertation has as its research subject the Curt Lange affair. The Curt Lange affair was a controversy related to Minas Gerais music from the 18th and 19th centuries, which took place in Brazil between 1958 and 1983 and involved several Brazilian musicologists, music critics, writers and politicians. Its main personage was the German,- Uruguayan-naturalized musicologist Francisco Curt Lange (1903-1997), that gives name to the controversy. Besides him, Renzo Massarani (1898-1975), Andrade Muricy (1895-1984) and Clovis Salgado (1906-1978) were also very important, of which the former two within the scope of music whereas the latter within the politics. The conflict took mainly place in the press, above all in newspapers of Rio de Janeiro, Minas Gerais and São Paulo, and its object of discussion consisted of two themes: the possession of Minas Gerais musical manuscripts by Curt Lange, papers of high historical value as national patrimony, and the editing criteria that this researcher conferred on these documents when he passed them to the format in a modern score, a process he called restoration. The thesis analyzes this episode that occurred in Brazilian history approching it effectively as a controversial phenomenon, a conception that ended up directing the work towards the consideration of linguistic and discursive elements in the face of the importance of language in the controversial events, in addition to questions concerning history and musicology. Started by a long introduction, which offers a presentation of the Curt Lange affair, information regarding the research trajectory and considerations about the theoretical and methodological architecture adopted, the work comprises two parts. The first part, although glossing over other temporal landmarks, such as the period in which Curt Lange knew and acquired the Minas Gerais manuscripts (1944-1946), concentrates mainly on texts related to the beginning of the controversy (1958-1959), analyzing controversial discourses and interactions. The second part, in turn, is less circumscribed to a date, analyzing more broadly the controversy and pertinent periods before and after it, adopting for such as a focus the musicologies involved in the conflict, the main subjects as well as the groups that rivaled. In both parts, in addition to texts published in the press, other types of material such as correspondence, articles in scientific journals, concert programs, books, photographs and even interviews with people who participated in the conflict were used as primary source documents. The analysis turns out to the conclusion that the thesis sustained throughout the work proved valid, that is, that the Curt Lange affair was symptomatic of a moment in which a more positive reception prevailed in the art of Brazil under the colonial period, transformation in which the music also was included.